Acceptance and commitment therapy group protocol for caregivers of anxious youth: an open trial pilot study - Raftery-Helmer, Jacquelyn N.; Hart, Ashley S.; Levitt, Madeline R.; Hodge, Steven M.; Coyne, Lisa W.; Moore, Phoebe S. (Frontiers in Child and Adolescent Psychiatry, 2024)
Anxiety disorders are common, distressing, and impairing for children and families. Cognitive-behavioral interventions targeting the role of family interactions in child anxiety treatment may be limited by lack of attention to antecedents to parental control; specifically, internal parent factors such as experiential avoidance and cognitive fusion. This pilot study evaluates the preliminary efficacy of a group-delivered caregiver treatment program, ACT for Parents of Anxious Children (ACT-PAC) that targets parental experiential avoidance, cognitive fusion, and child internalizing symptoms. Twenty three youth ages 7-17 years with a primary anxiety disorder diagnosis and their primary caregiver participated in six one-hour, weekly group treatment sessions. Parents and children reported on child symptomatology and parents reported on parent symptomatology and quality of life at two assessment points: within one week before ACT-PAC treatment and within one week after treatment. Parents self-reported on parental internal processes specifically targeted by ACT (e.g., cognitive fusion) weekly during the 6-week treatment. Results support the feasibility and acceptability of ACT-PAC and indicate reductions in parents' cognitive fusion and child internalizing symptoms.